2012
DOI: 10.1590/s0073-47212012000400007
|View full text |Cite
|
Sign up to set email alerts
|

Bird community in an Araucaria forest fragment in relation to changes in the surrounding landscape in Southern Brazil

Abstract: ABSTRACT. The dynamics of the bird community in a small forest fragment was evaluated along seven years in relation to changes in the surrounding landscape. The study area is an Araucaria forest fragment in Southern Brazil (state of Paraná). The sampling period covered the years 1988 through 1994 and the mark-release-recapture method was utilized. The landscape analysis was based on Landsat TM images, and changes in exotic tree plantations, native forest, open areas (agriculture, pasture, bare soil, and abando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 33 publications
0
3
0
3
Order By: Relevance
“…This pattern seems to be independent of the spatial extent of mixed forests, given that mixed forests form the second largest phytogeographical domain in the state. Previous studies have found that even small mixed forest remnants harbor rich bird assemblages, composed of many species that seem to use edge and forest interior indifferently [ 103 , [ 104 ]. For instance, Araucaria plantations–the dominant tree characterizing mixed forests–house sensitive and endemic birds associated with this forest type [ 105 ], [ 106 ].…”
Section: Discussionmentioning
confidence: 99%
“…This pattern seems to be independent of the spatial extent of mixed forests, given that mixed forests form the second largest phytogeographical domain in the state. Previous studies have found that even small mixed forest remnants harbor rich bird assemblages, composed of many species that seem to use edge and forest interior indifferently [ 103 , [ 104 ]. For instance, Araucaria plantations–the dominant tree characterizing mixed forests–house sensitive and endemic birds associated with this forest type [ 105 ], [ 106 ].…”
Section: Discussionmentioning
confidence: 99%
“…Embora seja enfatizado o caráter de limitação do uso de redes de neblina para estudos ornitológicos (Remsen & Good, 1996), trabalhos envolvendo a amostragem da avifauna de sub-bosque em florestas neotropicais são comuns (Karr, 1977;Blake, 1989;Verea et al, 2000;Machado & Fonseca, 2000;Verea & Solórzano, 2001;MalletRodrigues & Noronha, 2003;Scherer-Neto & Toledo, 2012;Loures-Ribeiro et al, 2011) e trazem resultados relevantes sobre a comunidade de aves. O uso de redes tem a vantagem de evitar registrar táxons de comportamento críptico e erros de observação (Karr, 1981;Rappolle et al, 1998;Sodhi et al, 2004;Barlow et al, 2006).…”
Section: Discussionunclassified
“…A lista de espécies apresentada segue CBRO (2014). A categoria trófica das aves foi determinada de acordo com revisão bibliográfica (Krügel e Anjos, 2000;Scherer et al, 2005). Foram consideradas nectarívoras (NEC) aves com alimentação composta em sua maior parte por néctar, granívoras (GRA) aquelas com alimentação composta em sua maior parte por grãos e frugívoras (FRU) com alimentação composta principalmente por frutos.…”
Section: Methodsunclassified